ESTIMASI NILAI PAJAK KENDARAAN SOLAR TERKAIT KERUGIAN PENCEMARAN UDARA (STUDI KASUS: METRO MINI DI DKI JAKARTA) - Laura Reviani Bestari; Aceng Hidayat; Mohammad Yani (Departemen Ekonomi Sumberdaya dan Lingkungan, Fakultas Ekonomi dan Manajemen, Institut Pertanian Bogor, 2014)
A total of 92% of diesel fuel consumption in Jakarta is dominated by public transportation, particularly medium-sized bus. Based on emission factor and distance value, the amount of emission from vehicle use is 17.078,27 tons of NO2, 15.786,63 tons of CO, 2.009,21 tons of PM10, and 1.334,69 tons of SO2, which give high risk to community’s health. The objectives of this research are: (1) to estimate air pollution loss value from diesel-fueled public transportation’s emission, and (2) to estimate tax value of diesel-fueled vehicle in Jakarta to internalize air pollution loss. The research method used was economic valuation analysis and internalization of economic loss. The estimation of economic loss from air pollution from Metro Mini emission based on pollutant cost is IDR 2,17 billion/year, while based on community’s health cost is IDR 12,45 billion/year. The estimation of tax value which internalized the loss from air pollution is IDR 1.301.955/vehicle/year (based on pollutant cost) or IDR 4.617.119/vehicle/year (based on community’s health cost).